2000
DOI: 10.1096/fj.99-1028com
|View full text |Cite
|
Sign up to set email alerts
|

GD3 ganglioside directly targets mitochondria in a bcl‐2‐controlled fashion

Abstract: Lipid and glycolipid diffusible mediators are involved in the intracellular progression and amplification of apoptotic signals. GD3 ganglioside is rapidly synthesized from accumulated ceramide after the clustering of death-inducing receptors and triggers apoptosis. Here we show that GD3 induces dissipation of DeltaPsim and swelling of isolated mitochondria, which results in the mitochondrial release of cytochrome c, apoptosis inducing factor, and caspase 9. Soluble factors released from GD3-treated mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(185 citation statements)
references
References 53 publications
8
177
0
Order By: Relevance
“…31 Till now, it was hypothesized that GD3 can contribute to the apoptotic program by directly targeting mitochondria in a Bcl-2-controlled manner and inducing the mitochondrial release of apoptogenic factors. 15 Our results provide the first evidence that GD3 acts at the level of the VDAC, where a local perturbation of specific mitochondrial lipid microdomains influencing the permeability transition pore complex and Cyt c release occurs. In this concern, a relevant role may be played by Bax and t-Bid, which relocate to lipid microdomains, as revealed by the analysis of linear sucrose gradient fractions from whole cells.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…31 Till now, it was hypothesized that GD3 can contribute to the apoptotic program by directly targeting mitochondria in a Bcl-2-controlled manner and inducing the mitochondrial release of apoptogenic factors. 15 Our results provide the first evidence that GD3 acts at the level of the VDAC, where a local perturbation of specific mitochondrial lipid microdomains influencing the permeability transition pore complex and Cyt c release occurs. In this concern, a relevant role may be played by Bax and t-Bid, which relocate to lipid microdomains, as revealed by the analysis of linear sucrose gradient fractions from whole cells.…”
Section: Discussionmentioning
confidence: 59%
“…13 Thus, GD3 has been reported to propagate CD95/Fas-mediated apoptotic signals 10,14 and act on the mitochondrial permeability transition pore, leading to cytochrome c (Cyt c) release. 15,16 However, the actual role of the GD3 action and its subcellular targets still remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…41 Rather, the cells overexpressing Bcl-2 displayed an enhanced survival upon ceramide treatment, 42 in agreement with previous reports. 43,44 Bcl-2 showed the expected heterogeneous distribution, most of it being located on the ER membrane. As to Ca 2 þ homeostasis (Figure 1), we detected a B30% reduction in the Ca 2 þ levels within the agonist-sensitive Ca 2 þ stores (i.e.…”
Section: Bcl-2 and Ca 2 þ : Establishing The Linkmentioning
confidence: 94%
“…5,87 Interestingly, Scorrano et al 84 have demonstrated that GD3 preferentially affect mitochondrial function, while other gangliosides such as GD1a, GM3 have no effect. Acetylation of GD3 nullifies its apoptotic effect and this mechanism is suggested to confer resistance to tumors.…”
Section: Gangliosides As Propagators Of the Er Stress-and Mitochondrimentioning
confidence: 99%